The determinants of foreign direct investment inflows into Malaysia / Jackson Saimun - Saimun, Jackson (2014)
This study investigate the determinants that might influence the foreign direct investment (FDI) inflows into Malaysia.There are several variables that has been indentified from literature that seen as important determinants towards FDI inflows into region. In this study.the inflation (Consumer Price Index),GDP per capita, labor cost are used because the availablity of the data and it has been argued by some of the previous researcher. The methodology used in this study is STATA SE 10 and Eviews7 with 23 years data starting from 1990 until 2012. The data obtain from World Bank data and Department of statistic Malaysia. The expected result from this study is there is significant relationship between inflation (Consumer Price Index). Gross Domestic Product (GDP) per capita, and labor cost, towards the FDI inflows into Malaysia.